COMMUNICATING REDD+ ISSUES AT LOCAL LEVEL: CREATING LATENT AND MANIFEST CONFLICT - Wibowo, Lukas Rumboko; Race, Digby; Curtis, Allan (Secretariat of Forestry Research and Development Agency, 2013)
âCarbon offsettingâin forestry-related projects is widely regarded as the ideal solution to the three challenges ofÂ Â the Â 21st Century: Â climate change, biodiversity conservation Â andsocio-economic development. At the same time, there is scepticism about the Reducing Emissions from Deforestation and Â Forest Â Degradation (REDD) Â proposalÂ particularly because ofÂ Â the Â weak Â governance and institutional capacities in many developing countries, which could jeopardize the delivery of benefits at the local level. One major problem is that most people have little knowledge on the causes and consequences of the climate change. This is partly because the information Â is largely scattered among scientific journals, and obscured by jargon and sophisticated Â mathematicalÂ models. Consequently, REDD+ is beyond thereach of Â manyof the people affected by REDD+. This Â paper examines the efforts and the capacity of Â the local governments and other development Â agents in explaining the REDD + issues and its impacts on the local people, especially customary communities. The research shows that lack of Â policy communication and promotion, as well as consultations with the affected groups arethe main contributing factors to latent and manifest conflicts. In turn, this conflicth as proven that NGOs, Â district governments and scientists have not been successful intermediaries. Thus, in the future policy communication on REDD+ should beaimed at improved network formation (i.e. between farmer groups with business partners and NGOs Â and other related actors), learning, negotiation and relationship building (i.e. between members of farmer groups, Â not only withtheir leaders within the farmer groups but also with governmental and business sectors). Policy communication should also create a Â new Â configuration ofÂ Â supportÂ and Â services in Â form Â ofÂ Â advocacy, empowerment and management skills and technical skills for conserving their natural resources, for adaptation to climate change and building more equitable governance and transparency at local level.